A Bumpy Road to Cities: Analysis of the Obstacles and Limits of China's New Urbanization*. (December 2015) - Kim, Jih‐Un
Abstract : In order to increase domestic consumption and thus improve economy, the current regime of China has designed a new urbanization, which is being pursued in two ways: granting urban hukou to rural migrants already in cities and relocating peasants to newly built or sprawled urban areas. In either way, the new urbanization of China faces major obstacles and limits in its implementation stage. For example, local governments, the de facto bearer of the project, seriously lack financial resources; big cities, where a large number of migrants are located, remain far beyond the scope of the hukou reform; the dislocated peasants have not received their full compensation at all; and, migrants or dislocated peasants, they are not guaranteed stable and decent jobs, a most critical source for more domestic consumption. To reach the ultimate goals of the new urbanization, the central government of China should effectively address those issues.